Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 1: 1722-1730 - Gottsched, Johann Christoph (Briefwechsel, 2015)
This edition, containing approx. 6,000 letters written to and by Johann Christoph Gottsched (and his wife Luise Adelgune Viktoria Gottsched), documents for the first time the correspondence of one of the most significant supporters of the Early German Enlightenment. This volume presents the complete 25-volume historic-critical edition of letters by the Saxonian Academy of Sciences in Leipzig. Each letter has been meticulously edited and includes detailed commentary about the writer, the occasion of the correspondence, as well as information about names and realities. The historical and biographical "venue" of each letter is described in detail.